Characterization of surface phenotypic molecules of teleost dendritic cells. Issue 1 (March 2015) - Shao, Tong; Zhu, Lv-Yun; Nie, Li; Shi, Wei; Dong, Wei-Ren; Xiang, Li-Xin; Shao, Jian-Zhong
Highlights We established a method for efficient enrichment of DrDCs. We identified the molecular phenotype of DrDCs as MHC-II+CD80/86+CD83+CD209+. We showed the molecular regulatory mechanisms in the antigen presentation of DrDCs.